Systematic review: risk factors of anxiety, depressiveness, and (lack of) social support in women and men prior to assisted reproduction = Systematisches Review: Risikofaktoren Ängstlichkeit, Depressivität und (mangelnde) soziale Unterstützung bei Frauen und Männern vor assistierter Reproduktion - Thanscheidt, Carla; Wischmann, Tewes (Geburtshilfe und Frauenheilkunde, 2023)
This review provides a systematic overview of the state of knowledge to date of psychosocial risk factors with a focus on anxiety, depressiveness, and (lack of) social support among - involuntarily childless women and men - prior to - assisted reproduction. The databases PubMed, PubPsych, PsycINFO-Ebsco, and Web of Science were searched for relevant publications in - English or German, and finally a total of 20 publications were included in the systematic review. Of these, 18 studies focused on depressiveness, 15 studies focused on anxiety, and 9 studies - focused on social support. Half of the studies included both men and women, while the other half included only women. Due to the large heterogeneity of the study results as well as - limitations, no clear conclusions can be drawn regarding a difference between the risk profiles of men and women with an unfulfilled desire to have children. However, it has been shown that - infertile couples or women experience higher levels of stress in the form of depressiveness and anxiety compared to fertile participants. Furthermore, it was found that social support, - regardless of gender difference, within the couple and from family and friends may be associated with a lower risk for depressiveness and anxiety.